Can Physical Exercise Improve the Residents' Health? - Li, Cong; Chen, Jin-Hong; Liu, Xi-Hua; Ren, Shu-Qi (Frontiers in Public Health, 2021)
This paper uses the 2018 data of the China Family Panel Studies (CFPS) to analyze the internal mechanism and influencing factors of participating in physical exercise on the health level of residents. The results show that participating in physical exercise can significantly improve the subjective and objective health level of residents. Heterogeneous test shows that the degree of influence of participation in physical exercise on the health level of residents varies according to the different regional and individual characteristics, the effect of urban residents’ physical exercise to improve their health level is better than that of rural residents, and the effect of physical exercise on the improvement of health level is more obvious in the eastern and western areas, those who have not completed compulsory education, and those with high incomes. This study will have strong guiding significance for the improvement of the overall level of national health in China, and provide theoretical basis and guiding opinions for the construction of healthy China.